The Efficacy of the AMKALA Method (Take Word Song) in Helping Pandemic Children Learn to Write Poetry - Moch. Sulchan (Jurnal Sinestesia, 2021)
The AMKALA technique of learning is a combined effort combining the approach of word shopping and the method of imagination suggestion. There has been no prior study on the AMKALA method's efficacy in teaching poetry at the high school level. As a result, it is required to undertake research to determine if the AMKALA approach is beneficial for teaching high school students to create poetry. Due to the fact that learning is not conducted face-to-face during this epidemic, it is possible to have challenges conducting an efficient learning program. The researcher is interested in determining the efficacy of the word shopping approach when combined with the imagination suggestion method from songs for teaching children to create poetry during the epidemic. The purpose of this research is to examine the efficacy of the AMKALA technique (take the word song) in teaching students at SMK AL BADAR to create poetry during the epidemic. This study was done at SMK AL BADAR. The study design was experimental with a pretest-posttest control group. This study examines two variables: (1) the independent variable, which takes the form of the "AMKALA" approach, and (2) the dependent variable, which takes the shape of poetry writing abilities. The population of this research included all pupils at SMK AL BADAR, and the sample size was one class divided into a control and an experimental division. The sample was drawn by lot, and from the results of the draw, all 32 kids of SMK AL BADAR were chosen. The data gathering approach used in this study is a test, specifically a poetry writing exam. Mann-Whitney test data analysis method. The results of the Mann-Whitney test on the posttest of the control and experimental classes revealed that; first, there is no statistically significant difference between the mastery of poetry writing skills of SMK AL BADAR students who are taught using the "AMKALA" method and those who are not taught using the "AMKALA" method. This is obvious from the Mann-Whitney test findings on the posttest scores for the control and experimental classes. The computation yielded a significance value of 0.938, which indicates that the value is not significant. Second, teaching kids at SMK AL BADAR to create poetry using the "AMKALA" approach is ineffective.